BEKERJANYA PERDA KOTA SEMARANG NO. 9 TAHUN 2013 TENTANG PENGATURAN PASAR TRADISIONAL DEMI BERLANGSUNGNYA KEADILAN DAN KESEJAHTERAAN (Studi Kasus Revitalisasi Pasar Rejomulyo) - Oscar Jago Dinasty Risan Pratama (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2018)
The problem that often arises today is the impartiality of the local governmentagainst traders in traditional markets that often lead to the implementation of localregulations that marginalize traders and traditional market participants. This alsohappens to traders in Kobong Market who are experiencing displacement by goingthrough a process that violates the procedure.The purpose of this study is to know, review and analyze the understanding ofSemarang municipal government related to the revitalization of fresh fish tradersRejomulyo Market for the sake of justice and welfare and the foundation of tradersdid not approve the transfer of traditional markets by the City GovernmentSemarang.Approach method in this research using socio-legal approach. Specification in thisresearch is qualitative naturalistic. The data used are primary and secondary data.Based on research results, Semarang City Government is less considering theinterests of the community, and consumers who need the supply of fish fromRejomulyo Market. The cornerstone of the traders did not approve the transfer oftraditional markets by Semarang City Government is the absence of clarity about theexact size of the stalls that will be accepted and the new market conditions areconsidered not feasible, and the violation of Article 35 paragraph 1 of the City ofSemarang Regulation no. 9 of 2013 on Traditional Market Arrangement and Article73 paragraph 1 of Regional Regulation of Semarang City No. 7 of 2010 on GreenOpen Space Arrangement.